Epidemiological characterization of individuals with human immunodeficiency vírus-1 in the state of Piauí, Brazil (Research, Society and Development, 2020)
This study was exploratory and retrospective through the study of secondary data on HIV infection in the municipality of Teresina-PI, from January 2008 to July 2010. Thus, this study aimed to characterize epidemiological variables, social and behavioral, factors related to individuals with HIV-1 virus in the state of Piauí. Data collection and research were developed at the Central Laboratory (Lacen). The sample consisted of 805 patients assisted at Lacen who presented positive serology for the HIV virus. Descriptive analysis of the 805 patients, 60% were male and 40% female. Of the total, 468 were between 31 and 50 years old, 221 between 18 and 30 years old and 115 over 51 years old. Regarding sexual preference was observed the process that has become common in Brazil as a whole, of "heterosexualization" totaling 80%, 8% said to be bisexual and only 12% homosexual. Most infected individuals assumed to use only “sometimes” condoms (46.3%) before contamination, 9.1% reported using condoms always and 44.6% reported never using them before infection. Regarding color / race, the patients declared themselves largely brown, 364 of the total, 270 as white, 168 as black, two yellow and one indigenous. In the variable level of education, it can be observed that 38 individuals reported not having any level of education, 526 had incomplete / complete elementary school, 176 had incomplete / complete high school and only 65 with incomplete / complete higher education. Thus, it is evident the need to implement measures aimed at expanding and disseminating educational information to the most diverse social classes.